FOOD WASTE CONTROL RECOMMENDATIONS IN INDONESIA BASED ON PUBLIC OPINION RELATED TO THE TARGET SDGS - Indriyani Rachman; Asyifa Imanda Septiana (Journal of Community Based Environmental Engineering and Management, 2020)
Food waste has an impact that can harm or disrupt human life. In Indonesia, food waste management has not been done in an integrated manner. This study was conducted to formulate recommendations for the proper handling of food waste for the people of Indonesia. Formulation of foodwaste management was carried out after collecting and processing data from respondents. Data on conditions and public opinion were obtained from 2 groups of respondents, namely the general public and environmental engineering students from several universities. Cluster analysis, AMOS approach and text mining were ulitzed as methods in data processing and analysis. The results showed that public opinion about knowledge of food waste is quite high. These recommendations for handling food waste are through the habits of food producers, the community as consumers, distribution of food before it expires, processing it into animal feed, processing it into an energy source with anaerobic digestion, and processing it into compost with good cooperation between waste collectors, companies composting and farmers using compost.